2005
DOI: 10.1111/j.1468-3148.2005.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot of a Gerontological Advanced Practice Nurse Preventive Intervention

Abstract: Background Persons with an intellectual and developmental disability frequently face barriers in accessing preventive services in community-based health care systems. As they age into middle years, they are at increased risk for functional decline. This paper presents a description of an advanced practice nurse (APN) intervention used in a pilot study that explored the feasibility of using an in-home preventive model based on a comprehensive geriatric assessment with persons ageing with an intellectual and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(64 citation statements)
references
References 36 publications
1
63
0
Order By: Relevance
“…The nursing faculty member had pilot tested a multidimensional health screening using screening tools commonly administered in a comprehensive geriatric assessment that have been pilot tested with adults with I/DD [19]. A social worker or service coordinator recruited persons aging with lifelong developmental disabilities to attend the health fair.…”
Section: Methodsmentioning
confidence: 99%
“…The nursing faculty member had pilot tested a multidimensional health screening using screening tools commonly administered in a comprehensive geriatric assessment that have been pilot tested with adults with I/DD [19]. A social worker or service coordinator recruited persons aging with lifelong developmental disabilities to attend the health fair.…”
Section: Methodsmentioning
confidence: 99%
“…8,9 A pilot study of preventative health monitoring by nurse practitioners found that 35% of adults aged 19-79 years with developmental disabilities living in a noninstitutional setting experienced a fall within a year's time period. 2 This percentage is higher than the one third of the general elderly population that falls each year. 1 Grant et al 3 found that 70% of community-dwelling adults aged 18-77 years with developmental disabilities had suffered a fall within the 5-year period of the study.…”
Section: Fall Risk In Individuals With Developmental Disabilitiesmentioning
confidence: 99%
“…1 Adults with developmental disabilities are at higher risk for injuries and falls as they age. [2][3][4] Additionally, there are indications that individuals with developmental disabilities experience some physiologic and degenerative changes associated with aging earlier than the general population, potentially putting them at higher risk for falls at relatively earlier ages. 5,6 Despite the fact that individuals with developmental disabilities are at increased risk, there is currently little information that pertains specifically to the assessment and prevention of falls for these individuals.…”
mentioning
confidence: 99%
“…While nurses have always held important roles in community and public health care, the literature has overlooked community nurses in the United States when it comes to caring for people with I/DD (Nehring, 2003). The scant research related to this topic focuses on the role of nurses in specific health promotion initiatives for people with I/DD (Cooper et al, 2006; Marks, Sisirak, & Chang, 2013), prevention services offered by advanced practice nurses (Hahn & Aronow, 2005), and guideline development for the implementation of community-based health promotion for individuals with I/DD (Drum et al, 2009). However, we still lack knowledge about the daily work of community nurses aiming to promote the healthy aging of individuals with I/DD living in the community.…”
Section: Role Of Nurses In the Communitymentioning
confidence: 99%